Indeks Malmquist: Studi Literatur dan Kajian Kinerja Perbankan Syariah - Supriyanto Supriyanto; Khaira Amalia Fachrudin; Handy Octavianus; Juli Meliza; Dina Hastalona; Taslim Taslim (Mahesa Research Center, 2021)
Measurement of Islamic Banking Performance using the Malmquist Index has been widely discussed by researchers from various countries. The Malmquist index is part of the Data Envelopment Analysis (DEA) method which is used to process non-parametric data to measure the increase in Decision Making Unit (DMU) productivity. This article aims to conduct a literature study of scientific articles that research the Malmquist Index. The research method used is Literature Study, starting with determining the research topic, then conducting theoretical studies and references related to the research carried out. 12 articles have been reviewed with the criteria of literature that has relevance to the research objectives, in the form of Scientific Journals, both National Scientific Journals, Accredited National Scientific Journals, International Scientific Journals, and Reputable International Scientific Journals. The results of the study reveal that Islamic banking has positive productivity growth, based on the area of Islamic Banking outside the Gulf Cooperation Council (GCC), has better performance. Sharia Banking in the Southeast Asia Region, represented by Malaysia and Indonesia, alternately, received the best ranking based on the ranking by the Islamic Finance Country Index (IFCI).